Preseason training improves perception of fatigue and recovery from a futsal training session - Wilke, C. F.; Wanner, S. P.; Penna, E. M.; Maia-Lima, A.; Santos, W. H.; Müller-Ribeiro, F. C.; Mendes, T. T.; Bruzzi, R. S.; Ramos, G. P.; Nakamura, F. Y.; Duffield, R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the posttraining recovery timeline of elite Brazilian futsal athletes before (Pre-PS) and after 10 weeks of the preseason (Post-PS) period of high-intensity technical-tactical training. Methods: At the start (n = 13) and at the end of the preseason (n = 7), under-20 male futsal players undertook fitness testing for maximal aerobic power, the countermovement jump (CMJ), and the 10-m sprint with change of direction. Furthermore, at both Pre-PS and Post-PS, the players participated in a training session where performance and psychophysiological measures were recorded before, immediately, 3, 24, and 48 hours postsession. The measures included CMJ, 10-m sprint, creatine kinase, Total Quality Recovery Scale, and Brunel Mood Scale. Effect size (ES) analyses compared fitness and posttraining recovery values for each parameter at Pre-PS versus Post-PS. Results: Only trivial ES (-0.02 to 0.11) was evident in maximal aerobic power, CMJ, and 10-m sprint at Post-PS compared with Pre-PS. For the timeline of recovery, only trivial and small ESs were evident for the 10-m sprint (-0.12 to 0.49), though CMJ recovery was improved at 3 hours (0.87) and 48 hours (1.27) at Post-PS and creatine kinase was lower at 48 hours (-1.33) at Post-PS. Perception of recovery was improved in Post-PS at 3 hours (1.50) and 24 hours postsession (0.92). Furthermore, perception of effort was lower immediately after the session (-0.29), fatigue was lower at 3 hours (-0.63), and vigor responses were improved in all postseason assessments (0.59 to 1.13). Conclusion: Despite minimal changes in fitness, preseason training attenuated players` perception of effort and fatigue and improved their recovery profile following a high-intensity technical-tactical training session.